2001
DOI: 10.1300/j069v20n01_06
|View full text |Cite
|
Sign up to set email alerts
|

Violent Behavior as Related to Use of Marijuana and Other Drugs

Abstract: ABSTRACT.The relationship of the degree of use of each of ten types of illicit drugs with each of eight types of violent criminal offenses, is reported for an African-American, inner-city, low SES, young adult study sample (N = 612). Prospective data from the time of birth was available for the statistical analyses, to provide 51 control variables on factors other than substance use which might predict to later violent behavior.Findings: Greater frequency of use of marijuana was found unexpectedly to be associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 23 publications
3
28
0
2
Order By: Relevance
“…Marijuana use is related to a number of risky behaviors that may result in aversive consequences to self or others, including crime, other drug use, risky driving, traffic accidents, and high-risk sexual activity (Brook et al, 1999;Cunningham et al, 2000;Friedman et al, 2001;Kingree et al, 2000). Despite the relationship between marijuana use and maladaptive risky behavior, few laboratory studies have investigated the relationship between marijuana intoxication and risk taking (Janowsky et al, 1976;Liguori et al, 1998;and Ramaekers et al, 2000 showed impaired riskrelated performance on driving/flying simulators).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marijuana use is related to a number of risky behaviors that may result in aversive consequences to self or others, including crime, other drug use, risky driving, traffic accidents, and high-risk sexual activity (Brook et al, 1999;Cunningham et al, 2000;Friedman et al, 2001;Kingree et al, 2000). Despite the relationship between marijuana use and maladaptive risky behavior, few laboratory studies have investigated the relationship between marijuana intoxication and risk taking (Janowsky et al, 1976;Liguori et al, 1998;and Ramaekers et al, 2000 showed impaired riskrelated performance on driving/flying simulators).…”
Section: Discussionmentioning
confidence: 99%
“…Early-onset marijuana use is related to later delinquency, having multiple sexual partners, and use of other drugs (Brook et al, 1999). Marijuana use is associated with criminal behavior, notably attempted homicide, drug trafficking, and delinquency in adolescents and young adults (Fergusson and Horwood, 1997;Friedman et al, 2001;Watts and Wright, 1990;White, 1991). Marijuana use has been associated with risky sexual behavior (Duncan et al, 1999;Kingree et al, 2000;Kingree and Betz, 2003;Staton et al, 1999) and chronic use may serve as a predictor for HIV risk (Malow et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This causes users to be highly vulnerable to clinical diseases, impulsive behavior, violence, and promiscuity, in order to obtain the drug. [4][5][6] The profile of crack users is generally young adults who are users of multiple PS, but adopt crack as their drug of choice. [7][8][9] The most common pattern of crack consumption described in the literature is characterized by loss of control, seeking behavior (despite obvious harm to various aspects of life), intense craving, and frequent relapses.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas considerable research has examined drug trafficking among gangs and high risk youth [8,9,10,11], this literature may have limited relevance for the large number of students who sell drugs yet remain relatively well-integrated into school and other social institutions. To date, however, few studies have examined drug selling among a general population of high school students [7,12].…”
mentioning
confidence: 99%